The Theoretical Foundations of Management of Intellectual Property of Industrial Enterprises - Sylka Ihor V. (Bìznes Inform, 2019)
The article is aimed at exploring differences in the definition of the essence of the concepts of «intellectual property», «objects of intellectual property», «management of intellectual property», and «approaches to management of intellectual property». Conceptual approaches to definition of the term of «intellectual property» as an economic and legal category, which actions are directed towards improving the profitability of enterprises and organizations, are considered; objects of intellectual property are grouped by industrial property and by creative-intellectual property; essence of the concept of «management of intellectual property» is defined depending on strategic and ongoing actions, taking into account the functions, components, management methods by which a positive financial result is achieved; it is accepted as feasible for enterprises to adopt a process-functional approach based on efficient management of the creation and use of intellectual property. On the basis of a generalization, a theoretical basis for the management of industrial enterprises is formed. Prospect for further research in this directions is to balance the process of developing, constructing, using or commercializing intellectual property in order to implement the functions of management of activities of industrial enterprises. Further development of the management of objects of intellectual property in accordance with the process-functional approach will improve the efficiency of production and profitability of enterprises.